2007
DOI: 10.1038/sj.onc.1210221
|View full text |Cite
|
Sign up to set email alerts
|

PTTG and PBF repress the human sodium iodide symporter

Abstract: The ability of the thyroid to accumulate iodide provides the basis for radioiodine ablation of differentiated thyroid cancers and their metastases. Most thyroid tumours exhibit reduced iodide uptake, although the mechanisms accounting for this remain poorly understood. Pituitary tumour transforming gene (PTTG) is a proto-oncogene implicated in the pathogenesis of thyroid tumours. We now show that PTTG and its binding factor PBF repress expression of sodium iodide symporter (NIS) messenger RNA (mRNA), and inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
56
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 63 publications
2
56
1
Order By: Relevance
“…Within this model, PTTG-mediated repression of iodide uptake was significantly abrogated by FGF-2 antibody treatment, suggesting that it is influenced by FGF-2 secretion, whereas repression by PBF remained unchanged, suggesting that this is independent of FGF-2 (Boelaert et al 2007).…”
Section: Pbf and Iodide Uptakementioning
confidence: 84%
See 4 more Smart Citations
“…Within this model, PTTG-mediated repression of iodide uptake was significantly abrogated by FGF-2 antibody treatment, suggesting that it is influenced by FGF-2 secretion, whereas repression by PBF remained unchanged, suggesting that this is independent of FGF-2 (Boelaert et al 2007).…”
Section: Pbf and Iodide Uptakementioning
confidence: 84%
“…The initial observation that PTTG may be involved in the regulation of iodide uptake led us to investigate the possibility of a similar role for PBF. We subsequently found that in our series of thyroid cancers, which demonstrated increased PTTG and PBF expression, NIS expression was significantly reduced compared with normal thyroid (Boelaert et al 2007), showing a significant negative correlation with both PTTG and PBF expression (K Boelaert, VE Smith, JA Franklyn, CJ McCabe unpublished data). Reduced NIS expression was also associated with early tumour recurrence and nodal involvement, further emphasising the importance of NIS activity in patient outcome (Boelaert et al 2007).…”
Section: Pbf and Iodide Uptakementioning
confidence: 95%
See 3 more Smart Citations